2004
DOI: 10.1093/jnen/63.8.856
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ischemic Injury of Astrocytes Is Mediated by Na-K-Cl Cotransport and not Ca2+Influx at a Key Point in White Matter Development

Abstract: Cerebral palsy is a common birth disorder that frequently involves ischemic-type injury to developing white matter (WM). Dead glial cells are a common feature of this injury and here we describe a novel form of acute ischemic cell death in developing WM astrocytes. Ischemia, modeled by the withdrawal of oxygen and glucose, evoked [Ca2+]i increases and cell death in astrocytes in post-natal day 10 (P10) rat optic nerve (RON). Removing extracellular Ca2+ prevented increases in [Ca2+]i but increased the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 54 publications
7
59
1
Order By: Relevance
“…In addition, the presence of functional GLT1 demonstrates the potential for transport-mediated glutamate release from these cells. Thomas et al (2004) also demonstrated a high resting intracellular glutamate levels in oligodendrocytes that was elevated following ischemia, suggesting both effective glutamate uptake under normal conditions and the absence of uptake reversal during ischaemia. It is not known how [Na + ] i , pH i and membrane potential are affected by ischemia in these cells but it would appear that the conditions are not met for significant reversal of glutamate uptake in this preparation (but see Back et al 2006).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, the presence of functional GLT1 demonstrates the potential for transport-mediated glutamate release from these cells. Thomas et al (2004) also demonstrated a high resting intracellular glutamate levels in oligodendrocytes that was elevated following ischemia, suggesting both effective glutamate uptake under normal conditions and the absence of uptake reversal during ischaemia. It is not known how [Na + ] i , pH i and membrane potential are affected by ischemia in these cells but it would appear that the conditions are not met for significant reversal of glutamate uptake in this preparation (but see Back et al 2006).…”
Section: Discussionmentioning
confidence: 88%
“…Average Daspartate uptake into astrocytes was higher than into any other cell compartment, although the degree of uptake varied considerably from cell to cell. Recent studies have shown rapid astrocyte swelling leading to necrosis in ischemic neonatal white matter, F o r P e e r R e v i e w 13 which will liberate astrocyte glutamate into the extracellular space in a glutamate transporter independent fashion (Thomas et al, 2004). In addition, the presence of functional GLT1 demonstrates the potential for transport-mediated glutamate release from these cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this point in development the mouse optic nerve was at a similar developmental point to the P10 rat optic nerves we have previously examined , with the majority of axons pre-myelinated ( Figures 3A and 3B). In most cases, glial cells could be readily identified using established criteria (see Materials and methods and Thomas et al, 2004). In control nerves perfused for 60 mins in aCSF before fixation, astrocyte processes radiated from the somata in the form of either thick primary processes or finer processes that originated directly from the somata or derived from branching of the primary processes.…”
Section: Ischemic Injury To Astrocytes In the Optic Nervementioning
confidence: 99%